Research on Chinese consumers' shell egg consumption preferences and the egg quality of functional eggs - Ruochen Chen; Caiyun Jiang; Xingzheng Li; Xuefeng Shi; Longyu Zhuang; Wenbin Zhou; Chen Zhou; Lin Xuan; Guiyun Xu; Jiangxia Zheng (Poultry Science, 2023)
ABSTRACT: The purpose of this study is to investigate the characteristics of egg consumption in China and the production of functional eggs, and finally enrich the types of shell egg products. Trial 1 explored the influence of egg quality on Chinese consumers' willingness to purchase eggs through a questionnaire, which investigated 1,317 consumers' preferences for egg appearance, factors influencing egg purchase, and purchase of functional eggs. The results showed that about 65% of respondents ate more than 4 eggs per wk, pink eggs were the most popular in China, about 65% of consumers preferred eggs with an egg weight of 48 to 58 grams. For functional eggs, 75.32% of consumers have never heard of them. Preferences for eggshell color and yolk color varied by geographic region, with darker colors preferred in Northeast China. Based on the survey results of functional eggs consumption in Trial 1, the dwarf layers of China Agricultural University were used in Trial 2 to produce functional eggs. The eggs are small and pink in color, which is in line with the preferences of Chinese consumers. Three hundred dwarf layers were divided into 4 groups, using the linseed oil added, marigold extract added, and yeast selenium added diets to produce normal, n-3 fatty acid-enriched, lutein-enriched and selenium-enriched eggs by feeding for 28 d, determined the eggs’ nutrient content and egg quality. The results showed that the n-3 fatty acid, lutein and selenium contents of the eggs of dwarf layers were significantly increased by changing the diets and did not affect the egg weight, eggshell strength, Haugh units or the proportion of egg parts. The results of this study are helpful to understand the trend of egg consumption preferences in China, and on this basis to produce functional eggs that meet the consumers’ expectations.